PENGARUH PERPUTARAN MODAL KERJA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (STIE Rajawali Purworejo, 2018)
The purpose of this study is to find out how big the influence of working capital turnover, liquidity, and solvency on profitability in basic and chemical industries listed on the BEI. The data used in this study consists of Quantitative data, ie data in the form of figures derived from corporate financial report data into the research sample, the accounting period December 31, 2015, and routinely published every year in the form of Indonesian Capital Market Directory (ICMD) which accessed through www.idx.co.id in the form of financial report data of compan ies incorporated in the cement sub-sector listed on the BEI period 2015.This research data is processed using the program SPSS 17.0. The research findings show that: partially Working Capital Turnover (WCT) does not have a very significant effect on Return On Investment (ROI), the significant value obtained 83.2% greater than 5%. Partially Current Ratio (CR) has no significant effecton Return On Investmen (ROI), because the level of significance obtained is greater than the standard used is 63.9% of 5%. Partially Debt to Equity Ratio (DER) has no significant effect on Return On Investment (ROI), because the level of significance obtained is greater than the standard usedie 27.9% from 5%. From F test, the result of Working Capital Turnover, Current Ratio and Solvency (Debt to Equity Ratio) simultaneously have no significant influence on profitability (Return on Investment). The significant level obtained is greater than the standard used ie 33.1% of 5%.